Тил билиминде дизбекли қоспа гәп теориясының айырым тартыслы мәселелери - Альниязов, А.И. (FAN va JAMIYAT, 2022)
In traditional linguistics, significant progress has been made in the study of compound sentences in the structural, semantic and functional aspects. The results of many years of research in this direction have not lost their significance in our time. However, in Turkic and Karakalpak linguistics, there are very few scientific works devoted to the study of the semantic properties of complex sentences in comparison with the study of complex sentences, moreover, conflicting opinions are expressed in the interpretation of the components of such sentences. The article summarizes the opinions of scientists about the linguistic status of a compound sentence, about the semantic relations between the components, etc., and expresses the author's attitude towards them.